557 Nasal cavity narrowing in pediatric obstructive sleep apnea. (3rd May 2021) - Cielo, Christopher; Vasisht, Shubha; Stefanovski, Darko; Whelan, Rachel; McDonough, Joseph; Tapia, Ignacio
Abstract: Introduction: The contribution of nasal cavity narrowing to obstructive sleep apnea (OSA) in children has not been well-defined. Acoustic rhinometry is a non-invasive technique that uses acoustic pulses to measure nasal cavity cross-sectional area (CSA) at defined distances from the tip of the naris. This study evaluated the relationship between nasal cavity CSA and OSA in children. We hypothesized that OSA severity would correlate with reduced nasal CSA. Methods: Children 5–12 years of age with OSA underwent polysomnography and acoustic rhinometry at baseline and after 3 months and 12 months of growth as part of a randomized controlled trial. Statistical analysis of the nasal cavity CSA up to 6 cm from the tip of the naris was performed using mixed-effects linear regression model with visit month, age at visit, trial number, OSA severity, and side (left or right naris), and statistical interaction between OAHI category and distance from the tip of the nose as a fixed effect and the random effects set on the level of individual subject. Least significant differences were used to account for multiple comparisons. An unbiased approach using latent class analysis was used to determine OSA severity categories based on obstructive apnea hypopnea index (OAHI). Post-hoc analysis was used assess the model adjusted (marginal) means and pairwise effects. Results: 112 participants completed testing (50% male, aged 7.9±2.1 years). Median (IQR) OAHI for subjects with mild OSA (n=69) was 4.4/hr (3.2), moderate OSA (n=35) was 9.7/hr (7.1), and severe OSA (n=8) was 21.3/hr (17.2). There was a significant difference in linear trend for nasal cavity narrowing of the CSA between patients with mild vs. moderate OSA, p=0.023. There was no difference in nasal cavity narrowing between the severe group and other groups, likely due to the small sample size of this group. Conclusion: There is a difference in the anterior nasal cavity narrowing between children with mild OSA and moderate OSA. In addition to structural narrowing from adenotonsillar hypertrophy, this may be another contributor to pediatric OSA. Support (if any): R01 HL120909 K23 HL135346 K01 HL130719